Comparison and Evaluation of Cross Platform Mobile Application Development Tools - Mehmet IŞITAN; Murat KOKLU (International Journal of Applied Methods in Electronics and Computers, 2020)
In order to develop a mobile application, it is necessary to develop software separately for each operating system to be outputted. In response to this problem, frameworks that can give application outputs for more than one operating system by developing applications on only one platform have been developed. With the recent diversification of these systems, which are called cross platform mobile application development tools, which one should be preferred has become a problem for developers. In this study, the cross-platform mobile application development tools that have come to the fore in recent years will be determined and evaluated separately based on the pros and cons of distinguishing parameters. With the help of the applications to be developed, values such as processor, memory, battery and network usage, rendering time, opening time, installation file size, application size will be measured. It is also aimed to help developers find out which framework is more suitable for their needs by comparing them on topics such as popularity, third party software support, operating systems that can be outputted, development languages and ease of use, speed - performance. In the study, it was observed that Flutter and React Native gave more successful results.